STRENGTH VARIATION IN M30 GRADE OF CONCRETE WITH PARTIAL REPLACEMENT OF POTABLE WATER BY TREATED WASTE WATER - Snehalatha, Bakshetty; Pasha, Maheboob; Trivikram, Ramesh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
Concrete is the generally used construction material in the world. Scarcity of water is perhaps the most critical environmental problem in several countries. Fresh water records for only 2.5% of the Earth’s water. The concrete industry alone usages over one trillion gallons of water each annually worldwide. In accumulation, the use of water for industrial purposes increases. So, it is important to conduct investigate of replacement of potable water by treatedwaste water partially or totally to produce concrete. The whole thing included severe laboratory experiments, for preparing concrete cubes with sewage treatment plant water from different points of the treatment process and different proportion in the preparation of concrete mixes. The strategy is to test reclaimed water samples in different blending with potable water by 0%,25%, 50%, 75% and 100%. Compressive strength, for concrete cubes was casted for 7 and 28days. Split tensile strength for 28 days. Results showed that the treated waste water tested in this study meet the requirements to be used in mixing concrete. Hence results suggested that treated waste water are suitable for using in construction industry.